PENGARUH MODEL PEMBELAJARAN TPS BERBANTUAN TTS TERHADAP HASIL BELAJAR AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS V SD GUGUS KOMPYANG SUJANA KECAMATAN DENPASAR UTARA TAHUN AJARAN 2018/2019 - I Kadek Tony Suantara (Guna Widya: Jurnal Pendidikan Hindu, 2020)
This research has a purpose to know the significant difference of Hindu Religion and moral science learning outcomes between students taught by learning model TPS combined with TTS game with students taught by conventional technique for 5 grades students at SD Gugus Kompyang Sujana Denpasar Utara year 2018/2019. This is a quasi-experimental research using non-equivalent posttest only control group design. The population was all 5 grades students at SD Gugus Kompyang Sujana Denpasar Utara year 2018/2019. The sample took SDN 4 Peguyangan which consist of 39 students as experimental group and SDN 3 Tonja which consist of 35 students as control group. Random sampling technique was used in choosing the sample. The data was collected by objective test in form of multiple choices. The collected data was analyzed by using inferential statistic (t-test). Based on the result of the analysis, it was obtained that tcalculated = 3,82 with significance level 5% and dk = 72 showed that ttable = 2,00. So, tcalculated = 3,82 > 2,00. The mean score of students taught by TPS combined with TTS game (????̅= 82,69) was better than students taught by conventional technique (????̅=73,94). It is concluded that learning model TPS combined with TTS game gave significant effect on Hindu Religion and moral science learning outcomes of 5 grades students at SD N Gugus Kompyang Sujana Denpasar Utara year 2018/2019.